2022
DOI: 10.1002/eji.202149771
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2‐specific T cells are generated in less than half of allogeneic HSCT recipients failing to seroconvert after COVID‐19 vaccination

Abstract: Little is known about the cellular immune response to SARS‐CoV‐2 vaccination in patients after HSCT and B‐NHL with iatrogenic B‐cell aplasia. In nonseroconverted HSCT patients, induction of specific T‐cell responses was assessed. The majority of allogeneic HSCT patients not showing humoral responses to vaccination also fail to mount antigen‐specific T‐cell responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…Vaccine efficacy in HSCT recipients: While highly immunogenic in the populations included in the large-scale studies that led to vaccine licensing, at least against the original outbreak strain of SARS-CoV-2, numerous, mostly single-center immunogenicity studies have demonstrated decreased, but highly variable, in vitro immune response in HSCT recipients to a 2- or 3-dose mRNA vaccine series as measured by neutralizing antibody and/or T-cell response [ 12 , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] ]. Not surprisingly, recency of HSCT, immunosuppressive therapy, lymphopenia, active malignancy and GVHD have all been demonstrated to be associated with dampened immune response.…”
Section: Vaccination In Hsct Recipientsmentioning
confidence: 99%
“…Vaccine efficacy in HSCT recipients: While highly immunogenic in the populations included in the large-scale studies that led to vaccine licensing, at least against the original outbreak strain of SARS-CoV-2, numerous, mostly single-center immunogenicity studies have demonstrated decreased, but highly variable, in vitro immune response in HSCT recipients to a 2- or 3-dose mRNA vaccine series as measured by neutralizing antibody and/or T-cell response [ 12 , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] ]. Not surprisingly, recency of HSCT, immunosuppressive therapy, lymphopenia, active malignancy and GVHD have all been demonstrated to be associated with dampened immune response.…”
Section: Vaccination In Hsct Recipientsmentioning
confidence: 99%
“…dose, associated with a larger pool of persistent memory T cells (103,104,106). Inferior results in allo-HSCT recipients as compared with a healthy control group could be explained, at least in part, by a more immature immune system with more frequent lymphopenia and the use of immunosuppressants or steroids, the same predictive factors as those reported in humoral response studies.…”
Section: Cellular Responsementioning
confidence: 89%
“…Currently, there are very few studies on immune responses after third vaccination in HSCT patients. Most studies focus on the humoral immune response, but point to the important role of cellular immunity, which we investigated [24][25][26]. Einarsdottir et al were the only investigators of the cellular immune response.…”
Section: Discussionmentioning
confidence: 99%